INCIDENCE OF JOHNE’S DISEASE AND HAEMONCHOSIS IN A SHEEP - Muralidharan, J; Saravanan , S; Ramesh , V; Kumar , V Ramesh Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An adult female Mecheri in an organized sheep farm exhibiting the signs suggestive of Johne’s disease was positive for the bacilli, Mycobacterium avium sub species paratuberculosis by Zeihl - Neelson technique and the haematological and serum biochemical parameters of the positive case were analyzed. The case on necropsy was confirmed for Johne’s disease by it’s characteristic gross lesions and histopathological findings. Faecal examination and necropsy revealed the concurrent infestation by the stomach worm, Haemonchus spp.